Creation of complexity assessment tool for patients receiving home care - Maria Leopoldina de Castro Villas Bôas; Helena Eri Shimizu; Mauro Niskier Sanchez (SciELO, 2016)
Abstract OBJECTIVE To create and validate a complexity assessment tool for patients receiving home care from a public health service. METHOD A diagnostic accuracy study, with estimates for the tool's validity and reliability. Measurements of sensitivity and specificity were considered when producing validity estimates. The resulting tool was used for testing. Assessment by a specialized team of home care professionals was used as the gold standard. In the tool's reliability study, the authors used the Kappa statistic. The tool's sensitivity and specificity were analyzed using various cut-off points. RESULTS On the best cut-off point-21-with the gold standard, a sensitivity of 75.5% was obtained, with the limits of confidence interval (95%) at 68.3% and 82.8% and specificity of 53.2%, with the limits of confidence interval (95%) at 43.8% and 62.7%. CONCLUSION The tool presented evidence of validity and reliability, possibly helping in service organization at patient admission, care type change, or support during the creation of care plans.